Implementation of human centered design (hcd) Models in designing web-based information systems - Mentari Tri Indah Rahmayani; Reno Firdaus; Peryoly Tekwana (Institute of Computer Science (IOCS), 2023)
The digital revolution has been able to change aspects of life. As of October 2020, the total number of cellphone users is 5.2 billion or 67% of the total world population (datareportal). The hospital is one of the public service institutions in the health sector that must implement good corporate governance and good clinical governance. Bengkalis Hospital is the only hospital located in Bengkalis Regency. Currently the registration of outpatients and inpatients is done manually, the patient or the patient's family must come in person to queue to pick up the registration number. Based on these problems, the authors will design a web-based hospital outpatient registration information system by applying the Human Centered Design (HCD) method. The Hcd method is a method with a problem approach that exists when the system is running with users and stake holders. this makes patients have to come earlier so they can get service faster and have to queue for hours just to take a registration number. The results of this study obtained the design of an information system that can be utilized by patients and staff/staff at Bengkalis Hospital in order to improve excellent service.